“Rape and GBV is part of the TRC's unfinished business!”: Illuminating a culture of impunity through tracing the legacy and collective memory of sexual violence in contemporary South Africa - Ntuli, Keabetsoe Luvano (Department of Political Studies, 2026)
The proliferation of sexual and gender-based violence (SGBV) in South Africa has ranked it as one of the countries with the highest rates of violence against women in the world – with interventions to address SGBV failing dismally to do so. A cursory glance at this issue may reveal that South Africa is in crisis, however, what underpins this crisis is the broader historical project of colonial and apartheid era crime and the culture of impunity that has surrounded this for decades. While the transition from apartheid saw substantial changes being brought about in the country, as part of the process of addressing past harms with a view of securing a peaceful and democratic future, the issue of gendered harm, particularly sexual violence, was depoliticised and deprioritised as an issue that needed to be acknowledged and accounted for in the historical record. Addressing the long-standing issue of sexual violence in South Africa, with a particular lens of understanding how sexual violence is political in the colonial and apartheid era, explores how a lack of accountability for this harm, fosters a culture of accountability and a dislocation of sexual violence in the collective memory.